4D synchrotron X-ray microtomography of fracture in nuclear graphite after neutron irradiation and radiolytic oxidation. (30th October 2020) - Wade-Zhu, J.; Krishna, R.; Bodey, A.J.; Davies, M.; Bourne, N.K.; Rau, C.; Davies, B.; Tzelepi, A.; Jones, A.N.; Marsden, B.J.; Mummery, P.M.
Abstract: Herein, the first study is presented using 4D synchrotron X-ray microtomography to capture all stages of crack development in neutron irradiated and radiolytically oxidised nuclear graphite. Employing a novel loading setup, specimens of Gilsocarbon graphite, both unirradiated and irradiated at 301 °C to 19.7 × 10 20 neutrons/cm 2 (∼2.6 displacements/atom ( dpa )), were loaded to generate a crack. All stages of the fracture process were then captured using synchrotron X-ray imaging. Reconstructed tomographic images and 3D segmented crack volumes have been used to observe and analyse the irradiation-induced evolution of the graphite microstructure as well as corresponding changes in the crack initiation, propagation, and arrest behaviour of graphite after neutron irradiation. Close examination of the applied stress-strain curves highlights the suppression of micro-crack-based damage accumulation in irradiated graphite. Moreover, as well as the crack-bridging and deflection mechanisms characteristic of unirradiated graphite, crack arrest in the irradiated graphite is shown to be significantly influenced by crack tip blunting. This change is associated with the growth of the open pore structure of graphite, specifically the enlargement and increased frequency of macro-pores, resulting from the simultaneous radiolytic oxidation of the graphite microstructure during neutron irradiation. Graphical abstract: Image 1